Use of Archive Material in the State Archives of the Republic of Macedonia and its Publishing Activity (Atlanti, 2016)
This paper is about the use of public archives in the State Archives of the Republic of Macedonia, with particular emphasis on publishing as one of the forms through which archival material is presented and distributed to the public. One of the roles of the State Archives of the Republic of Macedonia is to be a public service and should provide transparency and access to archival material stored in its repositories, which is largely achieved through the publication of collections of documents and monographs and is in accordance with existing legislation of the Republic of Macedonia, as well as with the laws of the State Archives.
Keywords: use; availability; publication of archival material; Act on publishing; Rules on publication; Commission for publication; State Archives of the Republic of Macedonia